Heparanase, a host gene that potently restricts retrovirus transcription - Brandon Waxman; Kyle Salka; Uddhav Timilsina; Supawadee Umthong; Deepak Shukla; Spyridon Stavrou (mBio)
ABSTRACT Heparanase (HPSE) is a heterodimeric β-D-glucuronidase that is critical in mammalian cells for the enzymatic cleavage of membrane-associated heparan sulfate moieties. Apart from its enzymatic function, HPSE has important non-enzymatic functions, which include transcriptional regulation, chromatin modification, and modulation of various signaling pathways. Interestingly, while HPSE is an interferon-stimulated gene, past reports have shown that it has proviral properties for many different viruses, including herpes simplex virus 1, as it assists virus release from infected cells. However, as of yet, no antiviral functions associated with HPSE have been described. Here, we show that HPSE utilizes a hitherto unknown mechanism to restrict retroviruses by targeting the step of proviral transcription. Moreover, we demonstrate that HPSE blocks transcription initiation by targeting the SP1 transcription factor. Finally, we illustrate that the antiretroviral effect of HPSE is independent of its enzymatic activity. This report describes a novel antiviral mechanism utilized by HPSE to inhibit retrovirus infection.IMPORTANCEHeparanase (HPSE) has emerged as an important factor that has proviral functions for a number of viruses, including herpes simplex virus and hepatitis C virus, by assisting in virus egress. However, HPSE is an interferon-stimulated gene and, thus, is a part of the host antiviral defense. Nothing is known about the antiviral functions of HPSE. Here, we examine in depth the role of HPSE during retrovirus infection using two retroviruses, human immunodeficiency virus type 1 (HIV-1) and murine leukemia virus. In this report, we show that mouse, but not human, HPSE blocks retrovirus infection by targeting provirus transcription. HPSE sequesters the SP1 transcription factor away from the proviral promoter, thereby inhibiting transcription initiation. In conclusion, our findings identify a novel antiviral function of HPSE and its potential role as an inhibitor of zoonotic transmission of retroviruses.